Attenuating effects of inflammatory pathway by prolonged left ventricular unloading after myocardial infarction in male rats - Jingwen Gao; Yasushige Shingu; Ryota Azuma; Satoru Wakasa (PLoS ONE, 2026)
Background Inflammatory response plays a pivotal role in myocardial injury and post-infarction remodeling after acute myocardial infarction (AMI). Mechanical unloading (UL) of the left ventricle (LV) has been proposed as a potential therapeutic strategy to preserve cardiac function; however, its effects on myocardial inflammation remain incompletely understood. Methods We employed a rat model of partial UL using heterotopic heart-lung transplantation following AMI. RNA sequencing (RNA-seq) was performed to evaluate transcriptomic changes, with a specific focus on inflammatory pathways in the non-infarcted remote area. Immune cell abundance was estimated using deconvolution analysis (QUANTISEQ). Quantitative PCR was performed to analyze some inflammatory cytokines, and macrophage polarization was evaluated by immunohistochemistry. Results AMI significantly impaired cardiac function, which was mitigated by UL. RNA-seq analysis revealed marked activation of inflammatory pathways and identified several hub genes involved in cytokine signaling following AMI, while these transcriptional changes were not significantly altered in UL groups after AMI. Immune cell profiling demonstrated an increase in M2 macrophages after AMI, while UL preserved M2 macrophage levels. Histological analysis further supported UL’s modulatory effect on macrophage polarization. Pro-inflammatory cytokines TNFα and IL1β were upregulated after AMI but showed attenuation with UL. Conclusion Partial UL potentially attenuates cardiac functional deterioration after AMI while exerting substantial effects on inflammatory gene expression and macrophage polarization. These findings suggest that the cardioprotective effects of UL may be correlated with the modulation of inflammatory pathways in the remote area after AMI.